2008
DOI: 10.1093/eurheartj/ehn533
|View full text |Cite
|
Sign up to set email alerts
|

Regular physical activity prevents development of left ventricular hypertrophy in hypertension

Abstract: Regular physical activity prevents the development of LVH in young stage 1 hypertensive subjects. This effect is independent from the reduction in blood pressure caused by exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 36 publications
2
31
0
3
Order By: Relevance
“…Reduction in insulin resistance, plasma norepinephrine, plasma renin and vascular resistance can be other explaining mechanisms 3334 . Physical activity can be used as a therapeutic choice for the treatment of hypertension and for prevention of its complications 35 , and it improves cardiac autonomic modulation and reduces risk of coronary heart diseases 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in insulin resistance, plasma norepinephrine, plasma renin and vascular resistance can be other explaining mechanisms 3334 . Physical activity can be used as a therapeutic choice for the treatment of hypertension and for prevention of its complications 35 , and it improves cardiac autonomic modulation and reduces risk of coronary heart diseases 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants were categorized as follows: White non-Hispanic, African American or Black non-Hispanic, Hispanic, or other race. At Wave III, participants were in young adulthood (age [18][19][20][21][22][23][24][25][26][27], where their personal socioeconomic status may not have been predictive of their actual SES, thus socioeconomic status was measured using parent-reported family income at Wave I. Income was grouped into the following tertiles: \$20,000 per year; between $20,000 and $60,000 per year; and over $60,000 per year.…”
Section: Covariatesmentioning
confidence: 99%
“…Moreover, consistent physical activity across the lifecourse has been linked to a number of beneficial health outcomes, including lower risk for hypertension and breast cancer [18,19]. Therefore, the purpose of this study was to examine whether physical activity patterns over the lifecourse impact birth outcomes, specifically preterm birth and low birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…However, an eight-year longitudinal study in mildly hypertensive individuals showed that chronic moderate physical activity did not actually induce physiological hypertrophic remodeling, but merely prevented pathological remodeling (Palatini et al 2009). Therefore, AET may improve or prevent cardiac remodeling following cardiac insults.…”
Section: Physiological Hypertrophymentioning
confidence: 99%